Correction: Health disparities in cervical cancer: Estimating geographic variations of disease burden and association with key socioeconomic and demographic factors in the US - Castellano, Tara; ElHabr, Andrew K.; Washington, Christina; Ting, Jie; Zhang, Yitong J.; Musa, Fernanda; Berksoy, Ezgi; Moore, Kathleen; Randall, Leslie; Chhatwal, Jagpreet; Ayer, Turgay; Leath, Charles A. (PloS one, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0307282.].